Nilai-Nilai Kekerabatan Dalihan Na Tolu untuk Mengarahkan Meaning of Life Siswa Perantau Beretnis Batak Mandailing Muslim - Suharto, Rachel Devita; Hidayah, Nur; Apriani, Rizka (Buletin Konseling Inovatif, 2025)
The Dalihan Na Tolu is a system of kinship that originated from the Muslim Mandailing Batak tribe regulating the life of people. This study aims to identify the role of Dalihan Na Tolu values as the kinship system as the fundamental for Muslim Mandailing Batak nomads students’ meaning of life fulfillment. This qualitative study used the phenomenology design. In collecting the primary data, we used observation and interviews with two Muslim Mandailing Batak nomads students. At the same time, the secondary data were obtained from the parents, siblings, friends, neighbors, and teachers. The data validity was assessed using triangulation on the observation and interview data. Our analysis results suggested that the Muslim Mandailing Batak nomads students’ meaning of life can be observed through three fundamentals of the meaning of life, namely the creativity, belief, and bravery values. The creativity value consists of the Marsitukkol Tukkolan Songon Suhat Di Robean value (asking the siblings to be successful) and Annakon Ki Do Hamoraon Di Au value (vengeance in learning). The belief value subsists of the speech or manner values in talking with the elders and Tua Mi U Jujung-jujung Tilako Mi U Dege-dege (disseminating kindness and covering the evils). Lastly, the behavior value consists of the bravery value.